Phylogeny of Potamogeton (Potamogetonaceae) revisited: implications for hybridization and introgression in Argentina - Ito, Yu (2016)
Potamogeton is a cosmopolitan genus of 90–95 species in which numerous hybridization events have occurred worldwide. A plant recently collected from Argentina exhibited ambiguous morphology that does not match any species of the genus. We aimed to assess if the plant coexisting with another Potamogeton species is a product of reticulate evolution. A concatenated plastid DNA (psbA-trnH, trnL intron, and trnL-trnF) and nuclear ribosomal DNA (5S-NTS) data sets, primarily based on previous studies sample set mainly consisting of American and Asian species, were analyzed using Bayesian inference. Nuclear ribosomal ITS sequences were also obtained from five Argentina materials. We recovered similar topologies from both the plastid DNA and nuclear ribosomal 5S-NTS analyses in which most specimens are consistently placed. The specimen of primal interest from Argentina strongly clustered with co-occurring linear-leaved species in the 5S-NTS tree, but was genetically identical to broad-leaved ones in the plastid DNA analysis. The ITS sequence of the specimen was the same as that of the linear-leaved species and no polymorphisms were observed. Considering the discrepant phylogenetic positions between the trees and lack of ITS infra-individual variations, the origin of the specimen from Argentina is better explained by hybridization and subsequent introgression.